Effects of a rehabilitative whole-body resistance band wrap on equine gait, posture, cortisol, and muscular function - Boger, Brooke; Naraian, Maegha; Hernandez, Emily; Eaton, Alexis; Rockburn, Ruby; Tillman, Isabella; Payne, Stesha; Yob, Chelsey; Panek, Char; Manfredi, Jane M. (Frontiers in Veterinary Science, 2026)
Resistance bands used while horses are exercised with their handlers have shown benefits, but it is unknown if whole-body resistance bands used independently have therapeutic benefits. This study hypothesized that horses with varying gait asymmetries would experience improvements in lameness, muscular function, range of motion, posture, and cortisol following short-term use of a whole-body resistance band wrap (RBW). In this study, nine lame adult horses were evaluated with and without the RBW. The assessment included: objective gait analysis, acoustic myography, postural analysis, gait kinematics, and salivary cortisol concentrations. Statistical analyses included: Shapiro–Wilk Test, Paired Student T-Tests or non-parametric Wilcoxon Signed-Rank Tests (significant at p < 0.05). There was no difference in lameness, velocity, or stride length. Cortisol levels were lower while wearing the RBW (p = 0.03). The RBW decreased semitendinosus muscle efficiency (EST Score, p = 0.008), and increased carpal (p = 0.03), tarsal (p = 0.03), and shoulder (p = 0.03) joint range of motion (ROM). Back angle increased when wearing the RBW (p = 0.04). These findings indicate the RBW has short-term effects on decreasing cortisol, improving joint ROM, and decreasing semitendinosus muscle function. Future studies exploring the use of the RBW with different exercise protocols are needed to further clarify its use for equine rehabilitation.